Dynamically growing neural network architecture for lifelong deep learning on the edge - Piyasena, Duvindu (2021)
Conventional deep learning models are trained once and deployed. However, models deployed in agents operating in dynamic environments need to constantly acquire new knowledge, while preventing catastrophic forgetting of previous knowledge. This ability is commonly referred to as lifelong learning. In this paper, we address the performance and resource challenges for realizing lifelong learning on edge devices. We propose a FPGA based architecture for a Self-Organization Neural Network (SONN), that in combination with a Convolutional Neural Network (CNN) can perform class-incremental lifelong learning for object classification. The proposed SONN architecture is capable of performing unsupervised learning on input features from the CNN by dynamically growing neurons and connections. In order to meet the tight constraints of edge computing, we introduce efficient scheduling methods to maximize resource reuse and parallelism, as well as approximate computing strategies. Experiments based on the Core50 dataset for continuous object recognition from video sequences demonstrated that the proposed FPGA architecture significantly outperforms CPU and GPU based implementations.